Antibacterial and Cytotoxic Effects of Moringa oleifera (Moringa) and Azadirachta indica (Neem) Methanolic Extracts against Strains of Enterococcus faecalis - Lucía Arévalo-Híjar; Miguel Ángel Aguilar-Luis; Stefany Caballero-García; Néstor Gonzáles-Soto; Juana Del Valle-Mendoza (International Journal of Dentistry)
Objective. To evaluate antibacterial and cytotoxic effect of 2 methanolic extracts of Azadirachta indica and Moringa oleifera against strains of Enterococcus faecalis (ATCC 29212) in vitro. Methods. The methanolic extracts of Azadirachta indica and Moringa oleifera were prepared in vitro. The antibacterial effect of the extracts against Enterococcus faecalis was evaluated using the agar diffusion technique. The minimum inhibitory concentration (MIC) was determined using the microdilution method and the cytotoxicity using the cellular line MDCK. Results. The methanolic extract with the most antibacterial effect during the first 24 and 48 hours against Enterococcus faecalis was Moringa oleifera, evidencing a growth inhibition zone of 35.5 ± 1.05 and 44.83 ± 0.98, respectively. The MIC for both extracts was 75 µg/ml. The bactericidal effect of the Azadirachta indica extract was found at a concentration of 25 µg/ml and a concentration of 75 µg/ml for Moringa extract. Conclusions. In conclusion, we demonstrated that the methanolic extract of Azadirachta indica and Moringa oleifera both have an antibacterial effect against Enterococcus faecalis strains during the first 24 and 48 hours. None of the extracts exhibited toxicity against the cell lines under low concentrations.